Factors Affecting Profitability of Food and Beverage Industries: A Resource-Based View and Competitiveness Approach - Chrisnando, Novian; Nilmawati, Nilmawati; Widjanarko, Hendro; Hikmah, Khoirul (Universitas Mercu Buana, 2024)
This study examines the determinants of profitability within Indonesia's food and beverage industry, specifically analyzing the role of firm size, liquidity, efficiency, leverage, and market power. Utilizing data from 24 companies listed on the Indonesia Stock Exchange from 2018-2022, the research employs multiple linear regression analysis to investigate these factors' impact on profitability, as indicated by Return On Assets (ROA). Results reveal that firm size, liquidity, efficiency, leverage, and market power collectively influence profitability, with market power emerging as the most significant determinant. While firm size and efficiency are positively associated with profitability, leverage negatively impacts it, and liquidity does not significantly affect it. The study's findings highlight the importance of strategic market positioning, operational efficiency, and prudent financial management in enhancing profitability.